Analisis Kelayakan Ekspansi Warung Makan “Salsabila” - Anvaulauvaa R, Rayvivant; Priambudi, Tunggul Wibisono; Nugraha, Oric Cipta; Purwati, Purwati; Inggarwati, Komala (Universitas Bunda Mulia, 2024)
This research discusses the potential for expansion of the